Determinants of demand for condoms to prevent HIV infections among barmaids and guesthouse workers in two districts, Tanzania. (December 2015) - Mubyazi, Godfrey; Exavery, Amon; Tenu, Filemoni; Massaga, Julius; Rugemalila, Jovitha; Malebo, Hamisi; Wiketye, Victor; Makundi, Emmanuel; Ikingura, Joyce; Mushi, Adiel; Malekia, Sia; Mziray, Abubakary; et al.
Abstract Background Condoms are scientifically recommended as potential products for preventing infections attributable to human immuno-deficiency viruses (HIV). However, evidence on factors leading to their inadequate use in developing countries is still scanty. This paper reports an exploratory study of factors constraining condoms use in Tanzania from the perspectives of barmaids, guest-house workers and retailers. Methods Data were collected in two districts—Mpwapwa in Dodoma Region and Mbeya Rural in Mbeya Region—between October and December 2011, using structured interviews with 238 individuals including barmaids, guesthouse workers and 145 retailers. Data analysis was performed using STATA 11 software. Results Awareness about condoms was high among all study groups. Male condoms were more popular and available than female ones. A considerable proportion of the barmaids and guesthouses were disappointed with condoms being promoted and distributed to young children and disliked condom use during sexual intercourse. Accessibility of condoms was reported as being lowered by condom prices, shortage of information concerning their availability; short supply of condoms; some people shying away to be watched by children or adult people while purchasing condoms; retailers' using bad languages to condom customers; occasionally condom shops/kiosks found closed when they are urgently needed; and prevailing social perception of condoms to have low/no protective efficacy. Regression analysis of data from barmaids and guesthouse-workers indicated variations in the degree of condom acceptability and methods used to promote condoms among respondents with different demographic characteristics. Conclusion A combination of psychosocial and economic factors was found contributing to lower the demand for and actual use of condoms in study communities. Concerted measures for promoting condom use need to address the demand challenges and making operational research an integral element of monitoring and evaluation of the launched interventions, hence widening the evidence for informed policy decisions.